MENGUNGKAP KESENJANGAN SOSIAL: Persepsi Siswa tentang Sikap Sosial di SMP Primbana Medan - Amal, Wan Muhammad Ichlasul (Islamijah: Journal of Islamic Social Sciences, 2024)
This study aims to describe students' perceptions of the social attitudes gap at Primbana Junior High School in Medan. The social attitude gap here refers to differences in the way students perceive and treat their peers based on social, economic and cultural backgrounds. This research used a qualitative approach with a descriptive method. Data were collected through in-depth interviews and observations of students in grades VII to IX at SMP Primbana Medan. The results showed that most of the students were aware of the social inequality in their school, which was reflected in discriminatory behaviours, stereotyping, and segregation of social groups based on economic status and race. However, there is also a segment of students who are trying to build an inclusive attitude and be more open to differences. Factors such as the influence of family environment, education and social interactions outside of school also influence students' perceptions of the social gap. This study illustrates the importance of more inclusive educational efforts and awareness of social diversity in the school environment, in order to create a more harmonious and respectful atmosphere among students.Keywords: Students' perceptions, social attitude gap, SMP Primbana Medan, discrimination, inclusiveness.